2014
DOI: 10.9790/3008-09132429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ramadan Fasting on the Ability of Serum, PBMC and Macrophages from Healthy Subjects to Kill M. Tuberculosis

Abstract: Objective: The objective of this study was to determine whether Ramadan fasting (RF) alters the ability of serum, peripheral blood mononuclear cells (PBMC) and macrophages to kill Mycobacterium tuberculosis (M. tb). Methods: Thirty healthy male volunteers who fasted during Ramadan participated in the study. Blood sampling was conducted seven days before and on the seventh and 21 st day of Ramadan. The following parameters were measured by ELISA: Complement C3, inducible nitric oxide synthase (iNOS), superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
(60 reference statements)
0
9
0
1
Order By: Relevance
“…Ramadan fasting was shown to enhance the killing ability of PBMC and macrophages against M. tuberculosis when compared to serum activity. There was no alteration on the serum levels of complement C3, iNOS, or SOD during Ramadan fasting ( 15 ). Furthermore, Ramadan fasting in a sample of 30 male patients was shown to enhance macrophagic killing abilities against tuberculosis ( 15 ).…”
Section: Immunity Changes In Healthy Individualsmentioning
confidence: 97%
“…Ramadan fasting was shown to enhance the killing ability of PBMC and macrophages against M. tuberculosis when compared to serum activity. There was no alteration on the serum levels of complement C3, iNOS, or SOD during Ramadan fasting ( 15 ). Furthermore, Ramadan fasting in a sample of 30 male patients was shown to enhance macrophagic killing abilities against tuberculosis ( 15 ).…”
Section: Immunity Changes In Healthy Individualsmentioning
confidence: 97%
“…A study tested the effect of Ramadan fasting on the body's ability to fight the pathogenic bacterial infection by Mycobacterium tuberculosis , which causes tuberculosis, of thirty fasting volunteers. [ 33 ] It demonstrated that fasting during Ramadan was associated with a reduction in pathogenicity of the bacteria by increasing the numbers of macrophages. The study also showed the ability of fasting to increase the secretion of INF-γ, which is known to stimulate the anti-microbial immune mechanisms against multiple bacterial and viral infections, as discussed above.…”
Section: Resultsmentioning
confidence: 99%
“… 23 The effects of fasting on oxidative stress have investigated by different groups by mean of assessing different markers of oxidative stress. Lahdimawan et al 24 reported that Ramadan altered classically activated macrophage regulation and signaling, reducing macrophage oxidative stress. In addition, Ibrahim and colleagues measured MDA, glutathione, glutathione peroxidase and catalase levels in individuals during Ramadan.…”
Section: Discussionmentioning
confidence: 99%